Giant nephrothoracic abscess: a misleading disease, a surgical challenge, and an unexpected complication - Kronenberg, P (2014)
A rare case of perinephric abscess with unilateral secondary pulmonary involvement that was further complicated by spillover of purulent content into the contralateral lung is reported here. Its diagnosis, treatment, and evolution are described and discussed along with certain features of nephropulmonary fistulas. The diagnosis of these abscesses is difficult, largely because of the paucity of primary symptoms and the frequent presence of misleading secondary symptoms. Deceptive cases like this one highlight the importance of its contemplation in every physician's differential diagnosis.